The multisensory experience of handling and reading books - Spence, CJ (Brill Academic Publishers, 2020)
The failure of e-books to take over from the traditional print format, as was so confidently predicted would happen only a few years ago, highlights how there is more to reading than merely the content of what we see. In fact, like any other object, the experience of interacting with a book, especially an old or historic volume, offers the reader the potential for a multisensory encounter. One that involves not only what the book looks and feels like, both the weight of the volume and the feel of the pages, but also the distinctive smell. In fact, one might also want to consider the particular sound made by the pages as they are turned over. However, it is the smell of older, and seemingly more olfactorily-redolent, works that appears to be especially effective at triggering nostalgic associations amongst readers. It is therefore only by understanding the multisensory nature of handling books, as stressed by this review, that one can really hope to fully appreciate the enduring appeal of the traditional format in the modern digital era. Several recent exhibitions that have attempted to engage their visitors by means of exploring the multisensory appeal of historic books or manuscripts in their collections are briefly discussed. While the multisensory mental imagery that is typically evoked by reading is unlikely to differ much between the print and e-book formats, there is nevertheless still some evidence to suggest that physical books can occasionally convey information more effectively than their digital counterparts.